2016
DOI: 10.1080/07853890.2016.1222451
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid change and modification of blood pressure and fasting plasma glucose in an overall healthy population sample: data from the Brisighella heart study

Abstract: It seems that SUA improvement could positively influence the age-related worsening of SBP and FPG in general population. Key messages Serum uric acid (SUA) is an emerging risk factor for incident hypertension and type 2 diabetes. SUA improvement could positively influence the age-related worsening of SBP and FPG in general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 34 publications
2
34
0
2
Order By: Relevance
“…However, this is the first study in which pre‐LT hyperuricemia is identified as a strong independent predictor of CV diseases among LT recipients. Among the general population, hyperuricemia is a recognized risk factor for CV events, including heart failure, and CV mortality, and importantly, uric acid–lowering agents have been shown to improve CV dysfunction and decrease the CV risk in the general population . This should be taken into account at the time of CV risk evaluation of candidates for LT and in the posttransplant management.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the first study in which pre‐LT hyperuricemia is identified as a strong independent predictor of CV diseases among LT recipients. Among the general population, hyperuricemia is a recognized risk factor for CV events, including heart failure, and CV mortality, and importantly, uric acid–lowering agents have been shown to improve CV dysfunction and decrease the CV risk in the general population . This should be taken into account at the time of CV risk evaluation of candidates for LT and in the posttransplant management.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the increase in blood UA levels in the general population has been associated with increased incidence of hypertension and diabetes [109], LDL oxidation [110], arterial stiffness [111], impaired cognitive function [112], and heart failure [113]. …”
Section: Evidence From Clinical Studies Relevance For Humansmentioning
confidence: 99%
“…Uric acid has proven emerging roles in various diseases such as gout, renal dysfunction, hypertension, hyperlipidemia, diabetes and obesity [47]. Hyperuricemia occurs as a result of the abnormal increased uric acid production and/or the impaired renal uric acid excretion [8].…”
Section: Introductionmentioning
confidence: 99%